2015
DOI: 10.3389/fphar.2015.00124
|View full text |Cite
|
Sign up to set email alerts
|

Different toxic effects of YTX in tumor K-562 and lymphoblastoid cell lines

Abstract: Yessotoxin (YTX) modulates cellular phosphodiesterases (PDEs). In this regard, opposite effects had been described in the tumor model K-562 cell line and fresh human lymphocytes in terms of cell viability, cyclic adenosine 3',5'-cyclic monophosphate (cAMP) production and protein expression after YTX treatment. Studies in depth of the pathways activated by YTX in K-562 cell line, have demonstrated the activation of two different cell death types, apoptosis, and autophagy after 24 and 48 h of treatment, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…In the erythroleukemia K-562 cell line the apoptotic cell death was activated after 24 h YTX incubation when the AKAP 149-PKA-PDE4A complex was located in the plasma membrane [ 55 ]. In these cells, variations of both intrinsic (Bcl2 and caspases 3) and extrinsic (caspase 8) apoptotic hallmarks had been showed after 24 h of YTX incubation, indicating the activation of these two types of apoptotic cell death [ 55 , 65 ]. After YTX exposure, no external ligands to activate death-inducing signaling complex (DISC) were described [ 66 ].…”
Section: Cellular Death and Ytxmentioning
confidence: 99%
See 2 more Smart Citations
“…In the erythroleukemia K-562 cell line the apoptotic cell death was activated after 24 h YTX incubation when the AKAP 149-PKA-PDE4A complex was located in the plasma membrane [ 55 ]. In these cells, variations of both intrinsic (Bcl2 and caspases 3) and extrinsic (caspase 8) apoptotic hallmarks had been showed after 24 h of YTX incubation, indicating the activation of these two types of apoptotic cell death [ 55 , 65 ]. After YTX exposure, no external ligands to activate death-inducing signaling complex (DISC) were described [ 66 ].…”
Section: Cellular Death and Ytxmentioning
confidence: 99%
“…The effect in cell viability was further studied in a lymphoblastoid cell line. This is a non-tumor model with normal apoptotic and mitotic machinery [ 65 ]. Again, opposite to tumor models, no cell death activation was observed in these cells after 24 or 48 h in the presence of YTX.…”
Section: Cellular Death and Ytxmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, previous studies in fresh human lymphocytes and K-562 lymphoma cells showed that they were, respectively, resistant and sensitive to YTX [14, 15]. Differential effects of YTX also showed that it does not induce cell death features in a lymphoblastoid cell line, whereas it induced apoptosis in the lymphocytic cell line K-562 [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, MTMR3 caused a reduced autophagic activity and smaller nascent autophagosomes when overexpressed (19). LC3A and LC3B are widely used as autophagy biomarkers, and the type I (16 kDa) is converted to type II (14 kDa) (43). A significant upregulation in the LC3-II/LC3-I ratio was observed in the present study following MTMR3 knockdown, implying an activation of autophagy.…”
Section: Discussionmentioning
confidence: 99%